The trouble with picket fences - Wilson, Teri (Wilson, Teri. Lovestruck, Vermont., 2021)
Pregnant and left behind by her ex-boyfriend, Melanie Carlisle just wants the picket fence around her house gone, while Cap McBride, with a teenager of his own, simply wants nothing to do with Melanie and her unborn child.